Influence of meteorological variables on the occurrence of pneumonia (Gestão & Regionalidade, 2021)
The causes of the influence of time and climate on living beings are not completely known, so studies that relate them to human health and strategies related to the formulation of public health policies are of great importance. This study aimed to analyze the influence of meteorological variables (precipitation, temperature and relative humidity) and the number of cases affected by pneumonia in the municipality of Campina Grande, PB in the period from 1998 to 2016. For this purpose, an epidemiological study was carried out, retrospective and descriptive with quantitative approach. The main contributions are configured as essential factors to understand the consequences that changes in climatic variables can have on the health of the population of the studied municipality. As a recommendation, the limitation of the study that relates to the underreporting of diseases, incorrect diagnoses, among others, which may occur with the departments responsible for providing health information, stands out.